Lactobacillus plantarum ZJUFB2 Prevents High Fat Diet-Induced Insulin Resistance in Association With Modulation of the Gut Microbiota - Hao Zhong (Frontiers Media S.A., 2021)
Lactobacillus plantarum ZJUFB2 is a novel probiotic isolate derived from Chinese traditional sourdough that possesses promising probiotics properties. This study aimed to investigate the effects of L. plantarum ZJUFB2 (B2) on insulin sensitivity using mice fed on a high-fat diet (HFD) as well as to explore the involved mechanisms. Purposely, male C57BL/6 mice continuously received an intervention of B2 (~109 CFU/day) for 16 weeks. The results showed that B2 treatment remarkably ameliorated insulin resistance and hyperglycemia in HFD-fed mice. The B2 intervention significantly decreased the hepatic lipid accumulation, serum low-density lipoproteins cholesterol, and lipopolysaccharides, and regulated the bile acids levels as well as liver mRNA expression involved in lipid metabolism. Moreover, the B2 intervention significantly changed the gut microbiota, specifically, showed a lower abundance of obesity-related and inflammation-associated microbes, e.g., Ruminococcus and Mogibacteriaceae. Furthermore, it exhibited a higher abundance of short-chain fatty acids and bile salt hydrolas-producing bacteria, such as Bifidobacterium and F16 compared with the HFD group. The findings of this study suggested that B2 is a novel probiotic, effective in preventing insulin resistance by improving the gut microbiota and bile acids.